Procedures for risk analysis and management in tunnelling projects - Zafirovski Zlatko; Gacevski Vasko; Lazarevska Marijana; Ognjenovic Slobodan (EDP Sciences - Web of Conferences, 2019)
The concept of risk analysis and management has a big impact and application in various branches of society. Today in civil engineering, especially in infrastructure projects this concept represents a serious matter that should not be avoided or delayed. There are different approaches and definitions for a risk, but it is important every problem to be reviewed separately. In tunneling the uncertainties and risks are always present, so appropriate measures and management should be considered and implemented.